A Systems Theory Re-Construction of Law and Religion. (19th December 2019) - Sandberg, Russell
Abstract: Law and Religion has rapidly developed as an academic sub-discipline in English and Welsh Law Schools in the 21st century amidst a significant amount of legislation, litigation, and public debate about religion. However, there are signs that this sub-discipline is becoming inward looking and stagnating. This article takes a step back and uses Niklas Luhmann's social systems theory to explore how Law and Religion has developed as a sub-discipline. Bringing together Luhmann's work on law and his work on religion, a systems theory of Law and Religion is developed for the first time. Deriving from but refining and developing social systems theory, the article argues that Law and Religion requires a radical rethink if it is to flourish as an area of study.